Detection of 3-4 Methylenedioxyamphetamine from Drug Abuser’s Fingers and Toenails using Liquid Chromatography with Mass Spectroscopy (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Nails can stably accumulate substances for extended periods of time, thus providing retrospective information regarding drug abuse and pharmaceutical use. In recent years, drug analysis in human nail clippings has proven its significant value in forensic toxicological applications, identification of in utero drug exposure, monitoring of drug treatment programmes, and therapeutic drug monitoring. Nails have various advantages over conventional matrices (blood and urine), which include a longer detection window (months to years), non-invasive sample collection, and easy storage and transportation. These aspects make nails a very significant matrix for forensic toxicology and therapeutic drug monitoring. Because of the low concentrations of drugs of abuse and pharmaceuticals present in nails and the complexity of the keratinized matrix, analytical techniques need to be more sensitive, and sample preparation is crucial. The aim of the present study is to develop a simple high-performance liquid chromatography-mass spectroscopy method for the identification and quantitation of 3,4-methylenedioxyamphetamine (MDA) in fingernail and toenail clippings. Finger and toenail clippings were collected from six users undergoing treatment at a rehab centre in Ujjain, M.P., India. Nail clippings were initially decontaminated, then hydrolyzed in 1 M NaOH at 370°C, extracted with ethyl acetate, diluted with methanol, and then subjected to LC-MS analysis. The calibration curve was constructed over the concentration range of 0.5 ng/mL to 30 ng/mL using the MDA reference standard. The limit of detection was calculated at 1.10 ng/mL and the limit of quantification recorded at 3.67 ng/mL in standard solutions, whereas the respective values in spiked nail clippings were 1.21 ng/mg and 4.6 ng/mg. Through the developed method, significant results have been obtained in original nail clippings with mean concentration ranges of 0.12 ng/mg in fingernails and 0.08 ng/mg in toenails in six abuser samples. The new method developed has been found to be capable of detecting the 3,4-methylendioxyamphetamine (MDA) drug in nail clippings even after 90 days of drug intake.